Mobile Learning Method (M-Learning) In University Students Based On Projects (Journal of Pharmaceutical Negative Results, 2023)
This article proposes a mobile learning procedure (m-Learning) in university students based on projects, which expresses as a scientific novelty the establishment of a path that links face-to-face and virtual teaching using mobile devices, through projects as a way of organizing the professional training process of university students. The research was oriented in a quantitative approach of pre-experimental type. The sample under study consisted of 100 students from the University of Holguín of the Mechanical Engineering career. They were used as methods documentary, systemic, observation analysis, the pedagogical pre-experiment, and the Chi-Square statistician (X2). After analyzing the data, it was found the existence of significant transformations in the learning of these students that generated favorable impacts in the productive and service processes in which they were inserted at work, concluding that this method from its external appearance and internal structure contributes to raising the quality of professional training for students in times of pandemic.